1980
DOI: 10.1021/bi00557a009
|View full text |Cite
|
Sign up to set email alerts
|

Positive cooperative binding of calcium to bovine brain calmodulin

Abstract: Equilibrium dialysis measurements of the binding of Ca2+ to calmodulin have confirmed the existence of four high affinity Ca2+-binding sites (Kd between 3 X 10(-6) and 2 X 10(-5) M). In the presence of 3 mM Mg2+, the dissociation constants for Ca2+ are increased two- to fourfold (Kd between 5 X 10(-6) and 4 X 10(-5) M). Positive cooperativity of Ca2+ binding was observed at low Ca2+ concentrations with Hill coefficients of 1.33 and 1.22 in the absence and presence of 3 mM Mg2+, respectively. The positive coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
160
1

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(183 citation statements)
references
References 44 publications
22
160
1
Order By: Relevance
“…Since the ~t~sities of the "3Cd NMR signal A and B are observed to increase in parallel as '13CdZ+ is successively added to calcium free calmodulin, this indicates that the individual high afftity binding constants, K& and K& are almost identical or that the 2 high affinity sites display positive cooperativity [26]. The same type of behaviour is observed for the 2 high affinity sites of rabbit skeletal muscle TnC P51.…”
Section: Discussionmentioning
confidence: 67%
“…Since the ~t~sities of the "3Cd NMR signal A and B are observed to increase in parallel as '13CdZ+ is successively added to calcium free calmodulin, this indicates that the individual high afftity binding constants, K& and K& are almost identical or that the 2 high affinity sites display positive cooperativity [26]. The same type of behaviour is observed for the 2 high affinity sites of rabbit skeletal muscle TnC P51.…”
Section: Discussionmentioning
confidence: 67%
“…Many investigators measuring calcium binding to calmodulin (16,18,28,42) have used an Adair function (43), or a modified version thereof, to describe calmodulin binding to calcium. This approach allows for different microscopic affinities for the four binding events and thus for detailed models of calcium binding to calmodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Each of these models reflects some properties of calmodulin and is reasonably applicable in contexts in which only these properties are relevant. However, none of these models can satisfactorily account for all of the observed properties of calmodulin such as cooperativity of calcium binding and different affinities for different calcium-binding sites (16), activation of targets by unsaturated calmodulin (17,18), and increased affinity for calcium upon binding to targets (18)(19)(20). We propose an alternative model, based on a biophysical description of the conformational transitions.…”
mentioning
confidence: 99%
“…Structural studies have shown that EF-hands are most often arranged in pairs, or higher order assemblies, with a short b-type interaction between the two 12-residue Caz+-binding loops. Pairs of EF-hands, either isolated or in the context of a larger globular domain, have repeatedly been found to bind Ca2+ ions with positive cooperativity, as for example in parvalbumin (Cave et al, 1979;Moeschler et al, 1980), troponin C (Grabarek et al, 1983;Teleman et al, 1983;Pearlstone et al, 1992), calmodulin (Crouch & Klee, 1980;Linse et al, 1990), calbindin Dgk , recoverin (Zozulya & Stryer, 1992), calerythrin (Bylsma et al, 1992), and sarcoplasmic calcium binding protein (Cox & Stein, 1981). However, gaining an understanding of the molecular mechanism underlying the observed cooperativity is an elaborate task involving detailed characterization of all ion ligation states.…”
mentioning
confidence: 99%